2021
DOI: 10.3847/1538-4357/ac0dc3
|View full text |Cite
|
Sign up to set email alerts
|

Misaligned Circumstellar Disks and Orbital Motion of the Young Binary XZ Tau

Abstract: We report our analyses of the multi-epoch (2015–2017) Atacama Large Millimeter/submillimeter Array (ALMA) archival data of the Class II binary system XZ Tau at Bands 3, 4, and 6. The millimeter dust-continuum images show compact, unresolved (r ≲ 15 au) circumstellar disks (CSDs) around the individual binary stars, XZ Tau A and B, with a projected separation of ∼39 au. The 12CO (2–1) emission associated with those CSDs traces the Keplerian rotations, whose rotational axes are misaligned with each other (P.A. ∼ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Qualitatively, the key difference between CBDs and circumstellar disks is that in former/latter, the binary torque is exerted at the inner/outer region of the disk, which contains small/larger amount of angular momentum, leading to relatively large/small warp and thus faster/slower viscous damping. Overall, these results are consistent with the observations that most CBDs are nearly coplanar with their host binaries (Czekala et al 2019), while circumstellar disks within young stellar binaries are often misaligned (e.g., Jensen & Akeson 2014, Ichikawa et al 2021.…”
Section: Disk Warping Breaking and Alignmentsupporting
confidence: 89%
“…Qualitatively, the key difference between CBDs and circumstellar disks is that in former/latter, the binary torque is exerted at the inner/outer region of the disk, which contains small/larger amount of angular momentum, leading to relatively large/small warp and thus faster/slower viscous damping. Overall, these results are consistent with the observations that most CBDs are nearly coplanar with their host binaries (Czekala et al 2019), while circumstellar disks within young stellar binaries are often misaligned (e.g., Jensen & Akeson 2014, Ichikawa et al 2021.…”
Section: Disk Warping Breaking and Alignmentsupporting
confidence: 89%
“…Absolute proper motions can, in principle, inform us about the relative masses of the two components in the binary, since the center of mass is closer to the more massive component, and therefore this component is expected to be the one that shows smaller absolute proper motions. However, when the system has a significant overall proper motion, which is not independently known, as in our case, disentangling both types of motions becomes extremely challenging unless the data cover a significant fraction of the orbital period (e.g., in XZ Tau: Carrasco-González et al 2009;Ichikawa et al 2021). We note that measuring the difference in the absolute proper motions of the two components of the A1-A2 IRAS 16293 −2422 binary is insufficient to derive the relative masses and that resolved gas kinematics is required for this purpose (see Maureira et al 2020 for details).…”
Section: Proper Motionsmentioning
confidence: 96%
“…So far, only for a limited number of these systems there is available (but partial) observational information about their physical properties, such as temperatures, kinematics (from radial velocities and proper motions), presence of circumbinary disks, stellar and disk masses (from dust and molecular emission and from dynamics), chemical properties, and interaction with the surrounding medium (e.g., outflows and interaction with the ambient molecular cloud, flyby encounters, and tidal interaction with nearby young stars). Some examples where these studies have been performed are the binary systems L1551 IRS 5 (Rodríguez et al 1998;Cruz-Sáenz de Miera et al 2019;Takakuwa et al 2020), RW Aur (Cabrit et al 2006;Rodriguez et al 2018), L1551 NE (Takakuwa et al 2014(Takakuwa et al , 2017, XZ Tau (Carrasco-González et al 2009;Zapata et al 2015;Osorio et al 2016;Ichikawa et al 2021), GG Tau (Phuong et al 2020), BHB2007 (Alves et al 2019), UX Tau (Zapata et al 2020), and IRAS 16293−2422 (Maureira et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Such disks are interesting to study to test photoevaporation models, but also for possible small scale cavities carved by giant planets at small orbits of a few au which have formed in situ. The only small cavity transition disk candidates studied at high resolution to date are CX Tau (Facchini et al 2019) which did not reveal an inner cavity, the ISO-Oph 2 secondary with a 2.2 au inner cavity (González-Ruilova et al 2020) and XZ Tau B (Osorio et al 2016) which revealed an inner cavity of 1.3 au radius, but this was not recovered in later high resolution observations (Ichikawa et al 2021). Small inner cavities 10 au were resolved in millimeter images of Sz 129 and MHO 6, despite not showing any indication of a dip in the SED (Andrews et al 2018a;Kurtovic et al 2021).…”
Section: Introductionmentioning
confidence: 98%